Gendered Experience in Public Space: Design as Tool of Empowerment towards Social Sustainability - YIU, Melody Hoi-lam; FUNG, Sze Wai Veera FUNG (MAJ - Malaysia Architectural Journal, 2025)
Although gender-inclusive design has received increasing awareness in recent years, the nominal consultation process tends to lack an in-depth understanding of female users’ genuine needs and experiences. A reason could be that women in Asian culture, especially those in domestic roles, are neither used to nor equipped to express themselves, therefore limiting their feedback to pre-established options. This paper investigates the gendered spatial experience and addresses the need for effective communication and creative expression by the undermined female voices. Current literature recognises the capacity of arts and cultural practice to engage and empower people, and this paper will demonstrate how the creative design process can be a form of gender empowerment through the case study of a public space design workshop in Hong Kong. While the immediate workshop findings describe the specific needs of female users in public spaces, this paper further reflects upon the programme design and process, with the results of establishing a framework to facilitate the expression and articulation of embodied gender experience. The paper concludes by highlighting domesticity in public space and how bodily engagement is essential in an experiential investigation to inform design. In response to growing literature and advocacy to foreground culture’s significance in social sustainability and gender issues, the research contributes to the discourse of gender empowerment through creative means and its position within the SDG framework.